Assessing the Violent Offending and Violent Victimization Overlap Among a Sample of Chinese Youth and Young Adults. (March 2019) - Wang, Xia; Cheon, Hyunjung; Beckman, Laura
Although an increasing number of studies have examined offending and victimization in China, little is known about the extent of the victim–offender overlap and what factors may explain differential tendencies toward offending versus victimization in the Chinese context. To fill this gap and to broaden the empirical base of the current literature on the victim–offender overlap, we examine the association of a number of prominent theoretical constructs with overall violent encounters and role differentiation. Using data collected from over 2, 000 students from six schools in Changzhi, a city in Northern China, and multilevel item response theory modeling, we find a nontrivial overlap between violent offending and victimization and differential tendencies toward offending versus victimization. We also find that most of our theoretical constructs are associated with overall violent encounters, but only moral beliefs, peer delinquency, drinking, and gender are related to role differentiation. Findings for theory and research are discussed.